2015
DOI: 10.1007/s11284-015-1263-5
|View full text |Cite
|
Sign up to set email alerts
|

Complex species distribution models of Goldcrests and Firecrests densities in Poland: are remote sensing‐based predictors sufficient?

Abstract: Species distribution models should identify ecological requirements of species and predict their spatial density. However, data from remote sensing sources are often used alone as predictors in modelling distributions. Such data will only produce accurate models if features that are distinguishable by remote sensing are a good match to the environmental traits that delineate habitat requirements. Both the Goldcrest Regulus regulus and the Firecrest Regulus ignicapilla respond to complex features of habitats th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Indeed, detailed data of environmental conditions might attenuate the coefficients we found. In contrast, it has been shown that even when modelling forest bird species distributions with very detailed forest structure data, the density of a bird species remains a significant predictor of the density of a close relative (Kosicki, Stachura, Ostrowska, & Rybska, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, detailed data of environmental conditions might attenuate the coefficients we found. In contrast, it has been shown that even when modelling forest bird species distributions with very detailed forest structure data, the density of a bird species remains a significant predictor of the density of a close relative (Kosicki, Stachura, Ostrowska, & Rybska, ).…”
Section: Discussionmentioning
confidence: 99%
“…The species density in grid cells was expressed as the Hayne estimator, calculated according to the equation below [6,[31][32][33][34]:…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…A study conducted on a small spatial scale suggested that habitat specialist species with narrow niches were more likely to be found in the core of patches with a simple shape, while generalist species tended to occur in the buffer zone of a more complicated shape [49,50]. Therefore, SDMs that use only the area of patches may not provide complete information on species' specific habitat preferences [7,24,33]. Indeed, this study confirmed and generalised the pattern on a large spatial scale, because when landscape configuration metrics were used as additional predictors, models turned out to be definitely better than models without them.…”
Section: Gams For Bird Species Density With and Without Landscape Conmentioning
confidence: 99%
See 2 more Smart Citations